CHOREOGRAPHING LANGUAGE LEARNING: PERFORMATIVE DYNAMICS OF AI AND COGNITIVE PEDAGOGY IN ENGLISH TEACHING - Raghavan, Lakshmi K.; Mary, D. Lourdhu; Sebastian, Mekha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The increasing use of Artificial Intelligence in education is setting the scene of dramatic change in the perception and performance of the English Language Teaching. It presents fresh opportunities of individualised studying and a pictorial rich, acting interactive involvement with language. Cognitive Linguistics studies how the language is related to human thinking and it gives us a dynamic script to this transformational combination. The article analyses the association of the cognitive linguistic theories in ELT and AI tools, with an investigation of their theatrical effects on pedagogy and learners. It uses qualitative data such as classroom observations read as performative enactments, journal entries written by students and notes made by teacher-researchers as assessment of effectiveness. The paper focuses on the following three questions: (1) What are the major benefits of using cognitive linguistic theories in ELT in the era of AI? (2) Do these staged approaches have any impact on teachers and students? (3) Are embodied cognitive linguistic methods able to deal with learning problems? The study concludes that AI that mimics the human cognitive patterns facilitates better understanding, better memory and self-directed learning, and redefines the role of the instructor as the orchestrator of advanced, performative pedagogical practices.